Regional Security in a Changing World - Kovačević, Marko (Journal of Regional Security, 2018)
Kupchan, Charles. 2012. No One’s World: The West, the Rising Rest and the Coming Global Turn. New York: Oxford University Press. 272 pp. $20 (Hardcover). Mahbubani, Kishore. 2013. The Great Convergence: Asia, the West and the Logic of One World. New York: Public Affairs. 315 pp. $27 (Hardcover).